The Impact of Pharmacist Intervention on Clinical Outcome, Adherence, and Quality of Life of Patients with Type 2 Diabetes Mellitus - Putri Fiari, Hera Zalia; Nasution, Azizah; Dalimunthe, Aminah (Indonesian Journal of Pharmaceutical and Clinical Research, 2022)
Diabetes Mellitus (DM) is a chronic disease that occurs when the body cannot produce enough insulin or cannot use insulin (insulin resistance) and diagnosed by measuring blood glucose level (BGL). BGLs of DM patients should always be controlled to prevent complications. The purpose of this analytical cohort study was to analyze the effect of pharmacy intervention (PI) on BGL, adherence, and quality of life (QOL) of DM Type 2 (T2DM) patients (n=48) admitted to Dr. Tengku Mansyur hospital in Tanjung Balai period December 2020 to May 2021. The BGL, adherence, and QOL of the patients were compared before and after PIs. The patients’ BGLs were recruited from their medical records, their adherence to medication was analyzed using MMAS-8 questionnaire, and the patients QOLs were analyzed using the EQ-5D-3L questionnaire and the scores were categorized into 3 categories (< 0.60 = bad, 0.6 - <0.80 = moderate, ≥0.80 = good). The obtained data were analyzed using descriptive and Wilcoxon Signed-Rank tests in the SPSS Program. Mean age of the patients was 59.20 ± 8.20 (years). Most (58.3%) of them were females. The mean BGLs (mg/dL) of the patients: before PI 1, 262.02±5.91; before PI 2, 259.39±5.53; after PI, 202.35±4.80; and follow up after PI, 168.60±3.07. The mean adherence scores: before PI 1, 4.833 ± 0.08; before PI 2 4.70±0.07; after PI 6.833±0.09; follow up after PI 7.793±0.05. The mean QOLs of the patients: before PI 1, 0.719±0.005; before PI 2, 0.719±0.001; after PI, 0.801±0.009; follow up after PI 0.977 ± 0.009. There were significant differences among BGLs, patients’ adherence, and their QOLs before and after PI. p=0.000 The present study proved that PI improved medication adherence, BGLs, and QOLs of outpatients with T2DM.